The relative efficacy of two brief treatments for sleep problems in young learning disabled (mentally retarded) children: a randomised controlled trial. - Montgomery, P; Stores, G; Wiggs, L (2004)
BACKGROUND: Settling and night waking problems are particularly prevalent, persistent, and generally considered difficult to treat in children with a learning disability, although intervention trials are few. Scarce resources, however, limit access to proven behavioural treatments. AIMS: To investigate the efficacy of a media based brief behavioural treatment of sleep problems in such children by comparing (1) face-to-face delivered treatment versus control and (2) booklet delivered treatment versus controls. METHODS: The parents of 66 severely learning disabled children aged 2-8 years with settling and/or night waking problems took part in a randomised controlled trial with a wait-list control group. Behavioural treatments were presented either conventionally face-to-face or by means of a 14 page easy to read illustrated booklet. A composite sleep disturbance score was derived from sleep diaries kept by parents. RESULTS: Both forms of treatment were almost equally effective compared with controls. Two thirds of children who were taking over 30 minutes to settle five or more times per week and waking at night for over 30 minutes four or more times per week improved on average to having such settling or night waking problems for only a few minutes or only once or twice per week (H = 34.174, df = 2, p<0.001). These improvements were maintained after six months. CONCLUSIONS: Booklet delivered behavioural treatments for sleep problems were as effective as face-to-face treatment for most children in this population.